Contribution of academician A.M. Grodzinsky to the problem of introduction and acclimatization of plants - T.M. Cherevchenko; S.I. Kuznetsov (Інтродукція Рослин, 2001)
Basic theoretical elaborations of A.M. Grodzinsky, Member of the NAS of Ukraine in the field of introduction and acclimatization of plants are cited.